Weak Underwater Signals’ Detection by the Unwrapped Instantaneous Phase - Aldo Vesnaver; Luca Baradello; Eleonora Denich (Journal of Marine Science and Engineering)
In marine seismic surveys, weak signals can be overlaid by stronger signals or even random noise. Detecting these signals can be challenging, especially when they are close to each other or partially overlapping. Several normalization methods have already been proposed, but they often lead to distortion. In this paper, we show that the unwrapped instantaneous phase of the associated analytical signal is an effective detection tool and validate it using synthetic and real data examples. This approach does not require user-defined parameters and therefore does not introduce personal bias in the results. We show that weak signals from submarine fluid plumes can be successfully detected by seismic surveys. These plumes can reveal anomalies in shallow sediments such as near-surface gas pockets and soft formations, which can severely affect offshore structures such as platforms and wind farms.